Thrasher, Tricia - (:unkn) unknown (My University, 2026)
I am a forward-thinking and highly driven researcher with 8+ years experience conducting studies on how various technologies impact learning. My background is in Applied Linguistics and I currently work as the Director of Research at Immerse, a virtual reality language learning company. I have also worked as French Program Manager and English Program Manager at Immerse. In my role as Director of Research, I lead the development of Immerse’s Research Agenda and manage our 30+ external research partners from universities around the world. I have also secured $100,000 in grant funding and $250,000 in virtual reality equipment from Meta to support VR implementation for language learning and research in underserved secondary schools throughout the U.S. Through this project, I work with partner schools to research Immerse's effectiveness, provide professional training to language teachers, and support VR implementation in classrooms. In my role as French Program Manager and English Program Manager, I was responsible for the development and launch of Immerse’s French and English programs. This included curriculum development, training and overseeing instructors, and monitoring the success of the program.